(untitled) (Acta Scientiarum. Animal Sciences, 2018)
This research aimed to determine the most appropriate thermal comfort index for buffaloes reared in the Eastern Amazon, Pará, Brazil. Twenty male Murrah buffaloes were used, and data on climate variables, rectal temperature (RT), body surface temperature (BST), and respiratory rate (RR) were recorded. Subsequently, the following indices were calculated: Temperature and Humidity Index (THI), Global Temperature and Humidity Index (GTHI), Benezra’s Thermal Comfort Index (BTCI), Ibéria’s Heat Tolerance Index (IHTI), the general, effective, and practical Buffalo Comfort Climatic Conditions Indices (BCCCIg, BCCCIe, and BCCCIp, respectively) and the general, effective, and practical Buffalo Environmental Comfort Indices (BECIg, BECIe, and BECIp, respectively) in the morning and afternoon. Higher values for THI, GTHI, RT, BST, RR, BTCI, BCCCIg, BCCCIe, BCCCIp, BECIg, BECIe, and BECIp were observed in the afternoon, and the highest IHTI values were found in the morning. A positive correlation was found among the physiological variables and THI, GTHI, BTCI, BCCCIg, BECIg, BCCCIe, BECIe, BCCCIp, BECIp, while a negative correlation was found for RT and BST with IHTI. The indices THI, GTHI, BCCCIg, BECIg, BCCCIe, BECIe, BCCCIp, and BECIp were determined to be very efficient to assess the thermal comfort status of buffaloes under the conditions of the present research.